Pengembangan Kebun Bibit Rumput Laut oleh Perempuan dengan Pemanfaatan Inovasi Jaring Horizontal: Development of Seaweed Seed Gardens by Women by Utilizing Horizontal Net Innovation - Kasim, Ma'ruf; Sudia, La Baco; Nurdiana, Nurdiana; Jalil, Wardha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Seaweed cultivation is an important activity in most coastal villages in Indonesia. Seaweed farming is mainly carried out by men, as longline fishing requires a lot of energy and can only be done by men. Women only help with small tasks such as tying and drying the seaweed. One of the most serious problems facing seaweed farmers is the presence of fish pests that attack the algae. This non-profit initiative aims to introduce innovations in seaweed farming to increase seaweed production and strengthen the role of women in seaweed farming. The horizontal net innovation prevents fish pests from attacking the seaweed during cultivation. This charity activity was carried out in one of the coastal villages in Eleke District, North Buton Local Government Area. This charity activity was carried out through training and operational support in the use of horizontal network devices. During the activity, it was noticed that residents, especially women, participated in the training with great enthusiasm. The activity was attended by 20 mothers representing seaweed farmers in the Ereke Local Government Area. This activity will lead to improved knowledge and skills in horizontal network management, especially women empowerment. It has been made easier for women seaweed farmers to design materials and produce horizontal nets directly. This horizontal net tool is very user-friendly and hassle-free to use.